2005
DOI: 10.1520/jai12468
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Long Service Exposures on the Thermal-Mechanical Behavior of Zy-4 and M5™ Alloys in LOCA Conditions

Abstract: The main objective of this paper is to describe the effects of a long service exposure of the PWR fuel cladding tubes on their thermal-mechanical properties during and after a hypothetical LOCA transient. Within this prospect, specific studies have been performed: on one hand, thermal ramp tests under uniaxial stress loading on as-received, pre-hydrided and irradiated samples of Zy-4 and M5™, and on the other hand, mechanical tests after high temperature oxidation and quench on as-received and prehydrided Zy-4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
31
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 8 publications
8
31
0
Order By: Relevance
“…9 together with the data for the unirradiated Zry-4 cladding [5]. The figure indicates that the rate constants of the M5 and Zry-4 alloys are equivalent at 1373 and 1473 K, and that that of the M5 alloy is lower at 1273 K. This agrees with the results by Portier et al [4]. Since the unirradiated MDA cladding showed a linear relationship between the measured weight gain and the square root of oxidation time, the rate constants were evaluated and plotted in the figure.…”
Section: Oxidation Kinetics Of the Advanced Alloy Claddingsupporting
confidence: 89%
See 1 more Smart Citation
“…9 together with the data for the unirradiated Zry-4 cladding [5]. The figure indicates that the rate constants of the M5 and Zry-4 alloys are equivalent at 1373 and 1473 K, and that that of the M5 alloy is lower at 1273 K. This agrees with the results by Portier et al [4]. Since the unirradiated MDA cladding showed a linear relationship between the measured weight gain and the square root of oxidation time, the rate constants were evaluated and plotted in the figure.…”
Section: Oxidation Kinetics Of the Advanced Alloy Claddingsupporting
confidence: 89%
“…Since the reaction at the cladding surface and the oxygen diffusion in the layers are the key processes of the oxidation, these high burnup factors may have an influence on the oxidation kinetics. Therefore, effects of those high-burnup factors have been investigated for unirradiated and irradiated Zircaloy cladding, and it was reported that the presence of a pre-corrosion layer may suppress the high-temperature oxidation, while the influence of pre-hydriding is very small [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…LOCA should be taken into account within the licensing procedures of the new developed Zr alloys for their application to a commercial reactor cladding [9]. Because the defects produced by an irradiation within the Zr matrix during a normal operation are regarded to anneal out rapidly at the beta phase temperatures in the process of a LOCA-like temperature oxidation, fortunately, the as-received cladding materials have usually been simulated in most LOCA tests [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…LOCA performance of the advanced Zr-based claddings has been investigated actively [9][10][11][12][13][14][15][16][17][18][19][20]. Portier reported a breakaway oxidation, in which a sudden or 'catastrophic' increase of the oxidation rate was observed, in the Zircaloy-4 and M5 claddings when they were steamoxidized for longer periods of more than 5000 s at 1000°C.…”
Section: Introductionmentioning
confidence: 99%
“…4,5) The tests have recently been performed with prehydrided nonirradiated cladding and high-burnup fuel cladding (70 GWd/t, <700 ppm) in order to confirm the safety of the high-burnup fuel and revise the criteria if necessary. [6][7][8][9][10][11] As a result, hydrogen produced the main burnup effect on embrittlement and the zero-ductility was seen at the oxidations much lower than the safety limit when the cladding absorbed hundreds of ppm of hydrogen, which is inconsistent with the results from the LOCA-simulated experiments.…”
Section: Introductionmentioning
confidence: 99%